Comparative Evaluation Antioxidant Potentials and Phenolic Composition of Ethanolic Extracts of Chromolaena odorata, Anacardium occidentale, and Phyllanthus amarus in Calabar - Okonkwo, Chibuzor Onyinye; Oko, Gregory Elayeche; Oyong, Nelson Bikom; Okonkwo, Sunday Nnamdi; Chukwu, Chizuruoke Oluomachi; Essien, David-Oku (Universitas Pendidikan Indonesia and Konsorsium Biologi Indonesia, 2025)
Oxidative stress contributes to the development of degenerative and metabolic diseases, and plants rich in phenolic compounds serve as natural antioxidants capable of mitigating its effects. This study comparatively evaluated the antioxidant potentials and phenolic composition of ethanolic leaf extracts of Chromolaena odorata, Anacardium occidentale, and Phyllanthus amarus harvested in Calabar, Cross River State, Nigeria. Standard in vitro assays were employed, including DPPH radical scavenging, ferric reducing antioxidant power (FRAP), hydrogen peroxide scavenging, catalase activity, and total phenolic content (TPC). The results revealed that A. occidentale exhibited the highest DPPH radical scavenging ability (30.93 ± 0.32%) followed by C. odorata (18.10 ± 0.72%) and P. amarus (9.48 ± 0.19%). However, P. amarus demonstrated the highest reducing and enzymatic antioxidant capacities, with FRAP (0.41 ± 0.01 µmol Fe²⁺/g), catalase (4.77 ± 0.12 µmol H₂O₂/min/mg), hydrogen peroxide scavenging (156.60 ± 1.42 µmol/mL), and TPC (2.97 ± 0.50 mg GAE/g). A. occidentale displayed moderate FRAP (0.14 ± 0.002 µmol Fe²⁺/g), catalase (3.30 ± 0.20 µmol H₂O₂/min/mg), hydrogen peroxide scavenging (90.90 ± 1.37 µmol/mL), and TPC (2.53 ± 0.56 mg GAE/g), while C. odorata recorded FRAP (0.28 ± 0.02 µmol Fe²⁺/g), catalase (4.30 ± 0.10 µmol H₂O₂/min/mg), hydrogen peroxide scavenging (116.07 ± 5.06 µmol/mL), and TPC (0.86 ± 0.01 mg GAE/g). A positive correlation was observed between TPC and antioxidant indices across species. The overall results indicate that P. amarus possesses superior total antioxidant capacity, suggesting its potential as a promising natural source of antioxidant compounds for pharmaceutical and nutraceutical applications.